A STUDY OF POSSIBLE RELATIONSHIP BETWEEN VITAMIN A AND SOME HEMATOPOIETIC FACTORS - B.Bozorgmehr; M.Ghaemi (Tehran University of Medical Sciences, 1982)
In a survey of 148 subjects (72 females and 76 males) in 3 villages and one city in Isfahan province, plasma vitamin A, hemoglobin concentration and hematocrit were determined in all subjects, and serum iron was measured in 19 persons, in order to investigate the possible relationship between vitamin A and hematopoietic factors. A positive correlation existed between plasma vitamin A and hemoglobin concentration. People with acceptable hemoglobin values had significantly higher plasma vitamin A levels compared to those with less-than-acceptable hemoglobin values. A direct correlation between plasma vitamin A and serum iron was also observed. The evidence gathered in this study supports the hypothesis that there is a direct relationship between anemia and vitamin A status of the subjects.